Controlling outsourced management accounting to build legitimacy - Lepistö S; Dobroszek J; Lepistö L; Zarzycka E (EMERALD GROUP PUBLISHING LTD, 2022)
PurposeThis paper aims to explore controls within an inter-organisational relationship involving outsourced management accounting services from the contractor's perspective.Design/methodology/approachQualitative data from within the relationship are analysed in a legitimacy-theory framework, illustrating how controls within the relationship are intended to build the contractor's legitimacy and what kinds of implications the controls have in relation to conflicts between interests inherent in the relationship.FindingsThe legitimacy perspective clarifies that while controls are aimed at ensuring efficiency for the client, they may also provide symbolic displays of the appropriateness of the contractor's actions both at an inter-organisational level for the client and at an individual level for the contractor's employees. While the contractor intends to build legitimacy with the client by demonstrating utility in the form of efficiency, the process also gives the client influence and allows the disposition in terms of shared values to be demonstrated. However, this process has some negative consequences for the contractor's employees as it is insufficient for serving the boundary-spanning employees' interests connected with the nature of their work. Hence, the same controls need to yield benefits and fair outcomes for employees. The controls simultaneously foster interconnections that contribute to permanence and formalise the outsourcing of complex services, thereby rendering such processes comprehensible and transferable to other settings, which can be seen to serve the contractor's continuity interests.Originality/valueThe paper contributes to academic research by illustrating how controls within inter-organisational relationships not only steer boundary-spanners' work to conform to a client's needs but may also help to build legitimacy via symbolic properties in the presence of conflicting interests at both an inter-organisational and individual level. It specifically highlights the important role of boundary-spanners lower in the organisational structure, who both affect and are influenced by the intentions to build legitimacy with the client.